HUBUNGAN KEPUTUSAN KARIER DENGAN KEMATANGAN EMOSI PESERTA DIDIK KELAS IX SMPN 1 GARUT - Sumiati sumiati; Teti Sobari; Siti Fatimah (IKIP Siliwangi, 2021)
Emotionally mature students tend to make career decisions that are right for themselves because they are able to think objectively about the various options available, so they can be responsible for the decisions taken. The purpose of this study is to determine the relationship between emotional maturity and career decisions of students in continuing education at the next level. The research method used is ex post facto quantitative method with correlational research type. The number of samples in this study were 100 class IX students. Collecting data using emotional maturity scale and career decision scale using a Likert scale model. The data from the scale in this study are quantitative data which will be analyzed descriptively in percentage. The results showed the significant correlation between emotional maturity and career decision making was 0.000 with a person correlation value of 0.762 in a positive direction so that it can be concluded that in this study H0 is accepted and Ha is rejected, meaning that there is a significant relationship between emotional maturity and career decision making in class students. IX SMPN 1 Garut. This figure shows a positive relationship with a strong level of relationship. From these results it can be interpreted that the high emotional maturity is one of the aspects that increase career decision making, or vice versaKeywords: emotional maturity, career decisions.